Peningkatan Hasil Belajar Peserta Didik Melalui Penerapan Model Problem Based Learning Kelas IV UPTD SDN 01 Mungka - Maisal Hayani; Syawaluddin Syawaluddin; Deslita Deslita; Amiruddin Amiruddin; Dian Nuraga; Refi Fitria (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the low learning outcomes of fourth grade students of SD UPTD SDN 01 Mungka. This study aims to improve the learning outcomes of fourth grade students of UPTD SDN 01 Mungka through the Cooperative Learning method. The type of research used is Classroom Action Research (CAR) with the Problem Based Learning (PBL) model. The method used in the study is two cycles, namely the Cooperative Learning method. Each cycle consists of 4 stages, namely planning, implementation/action, observation/observation, and reflection. Each cycle consists of one meeting (3 lesson hours). The population used is 10 people. Data collection techniques used are observation, tests and interviews. The results of this study show an increase in student learning outcomes from pre-action, cycle I and cycle II. The learning outcomes of students at the pre-action stage were 42%, in cycle I (first) increased to 67%, in cycle II (second) also increased to 92%. Thus, a recommendation can be submitted that the application of the Cooperative Learning method can improve student learning outcomes in Islamic Religious Education material for the 2024/2025 Academic Year.